Corporate Governance Mechanisms and ESG Disclosure: Evidence from Emerging Financial Markets - Rudolph, Makhathini Lungani; Aliamutu, Kansilembo (International Journal of Economics and Financial Issues, 2026)
The study explored the influence of corporate governance structures and business location on the correlation between ESG disclosure and firm performance among firms listed on the Johannesburg Stock Exchange. The study uses a quantitative strategy that uses panel data analysis to address unobservable heterogeneity and make estimates more accurate over time. This method is appropriate because it considers differences across companies, changes over time, and the way that corporate governance frameworks, ESG disclosure, and business performance affect each other. A fixed effects panel regression is employed to assess the claimed associations. The results offer detailed insights into the influence of governance quality and information settings on the financial consequences of sustainability reporting in an emerging market context. ESG disclosure appears to correlate negatively with performance in enterprises situated in financial centres, indicating that market participants in these locales may view substantial ESG investments as a distraction from profit-maximizing endeavours. Companies outside financial centres have a decreased or neutral link between ESG and performance, suggesting that disclosure serves mainly as a reputational or regulatory activity rather than a catalyst for financial performance. Robust governance systems improve business performance in financial hubs but seem ineffectual in less stable institutional contexts, highlighting the significance of regulatory enforcement and board autonomy. These findings together highlight that the robustness of corporate governance, company size, and geographic location collectively influence the impact of ESG disclosure on firm value in South Africa’s growing financial markets.